Workshop Summary: Developing Northern Bobwhite Management Plans - A Habitat-Based Framework - Brad S. Mueller (National Quail Symposium Proceedings, 2017)
Successful northern bobwhite (Colinus virginianus) management is a complex and often expensive process that requires careful planning and a well-designed habitat management program. Written management plans are often used by landowners who wish to maximize quail populations on their property. Although management plans are as varied as the individuals who write them, a successful plan should: (1) be chronologically based, (2) contain an associated budget, and; (3) combine the objectives of the landowner with the limitations and potential of the individual property. The goal of a management plan is to insure that habitat modifications proceed in a well-designed, cost-effective, and orderly fashion. Although this paper focuses on developing management plans for northern bobwhite, the concepts presented here can be used to develop management plans for other species of quails in the United States.